1990
DOI: 10.1111/j.1365-2621.1990.tb06779.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Activity of Water in Casein Model Systems as Determined by 2H NMR and Sorption Isotherms

Abstract: Two means of monitoring water availability in casein model systems were compared. Adsorption isotherms of rennet casein and freezedried casein-sodium chloride (NaCI) (95:5 ratio) were obtained over the a, range 0.43 to 0.85. Over the entire a,,. range the casein-NaC1 samples s&bed more water than the casein only samples. Deuterium (7H) Nuclear Majrnetic Resonance (NMR1 R, and R, relaxation na-;a&eters were measured in the samd casein model systems. A lin'ear relation between a, and both II1 and R2 was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It is characteristic of inorganic or organic porous materials. A similar pattern was found in previous food science studies focusing on model molecules such as casein, lactoglobulin (Fanni et al, 1989;Curme et al, 1990) or on more heterogeneous material such as meat (Kabil et al, 2012). Plant litter's ability to adsorb water is a property of huge importance, enhancing habitat conditions for plants, micro invertebrates and microorganisms in litters and soils (Henry, 2012;Kammer et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is characteristic of inorganic or organic porous materials. A similar pattern was found in previous food science studies focusing on model molecules such as casein, lactoglobulin (Fanni et al, 1989;Curme et al, 1990) or on more heterogeneous material such as meat (Kabil et al, 2012). Plant litter's ability to adsorb water is a property of huge importance, enhancing habitat conditions for plants, micro invertebrates and microorganisms in litters and soils (Henry, 2012;Kammer et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…The threshold found (a w ¼ 0.75) can be explained by the fact that below this value, NaCl crystallizes and can no longer adsorb water molecules. Previous studies (Curme et al, 1990;Fanni et al, 1989) showed that when NaCl was added to proteins such as casein or blactoglobuline, NaCl ceased to adsorb water below a w ¼ 0.75, actually turning into a crystal. The findings here are of importance, demonstrating that exposure to NaCl (from 35 g.L À1 ) aggravates matric stresses (due to desiccation) in litters above a certain a w threshold (0.75), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Schnepf (2) reviewed the types of bonding between water and protein molecules, and how their interaction relates to these functional properties. Numerous methods for assessing protein hydration include dielectric studies (3), nuclear magnetic resonance (4)(5)(6)(7)(8) and calorimetry (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…However, it was noted from the results that the samples suffered a significant increase in the moisture content at feed salt concentrations below 10% w/w where the total soluble solids content dropped not so much. Higher moisture content of the spray-dried-fish sauce powder in this case might be a result of lower electrolyte concentration, which led to a significant decrease in the number of rotationally mobile water molecules (Curme et al, 1990;Schuck et al, 1999), resulting in higher residual moisture content.…”
Section: Moisture Contentmentioning
confidence: 94%
“…When the feed salt concentration was reduced to 2% w/w, particles with dimpled and collapsed structure were formed. This is a result of an increase in bound water at lower electrolyte concentration (Curme et al, 1990;Schuck et al, 1999); thus the water was removed more slowly and the skin remained highly moist for a longer period of time. As a result, the hollow particles dimpled and collapsed as they cooled (Nijdam and Langrish, 2005).…”
Section: Morphologymentioning
confidence: 98%